Analysis of Portfolio Investment in Indonesia Macroeconomy - Atyantodito, Ihsan bagus; Firmansyah, Firmansyah (Universitas Negeri Semarang, 2020)
This research examines the cause of portfolio flows in Indonesia and the effect of portfolio flows to the Indonesian economy based on monetary policy approach. By analyze the interactions among portfolio investment, global and domestic macroeconomy, and financial variables by employing a structural vector autoregression model, this study finds: 1) that both global and domestic factors play the role in driving the portfolio flows in Indonesia; 2) the portfolio flows play the role in driving the domestic financial market, by the order starts from asset prices, followed by exchange rate and lastly credit; 3) the portfolio flows play a role in driving the Indonesian economic growth. The percentage of the effect of portfolio is relatively large compared to the other variables, but in total, the percentage of portfolio flows in driving the economic growth is quite small. Nonetheless, the impulse response function result shows that the shock in portfolio flow can affect the economic growth.